PENINGKATAN KOMPETENSI KARYAWAN DAN SAFETY CULTURE MELALUI LEARNING MANAGEMENT SYSTEM “SINTESIS+” SEBAGAI KONTROL OPERASIONAL - Chandra Singgih Pitoyo; Yuristian Yuristian; Cahyo Andrianto; Riza Rahmah Angelia (Indonesian Mining Professionals Journal, 2019)
With 118.400 hectare of concession area and employed people for more than 21.694 employees within company and from business partners, Berau Coal needs to put more concern in managing operational and health, safety and environment (SHE). The challenges that need to be faced are location that scattered into 4 operational areas, limited time for employess to access information because most of time exploitated for working, various educational background, and technology literacy. Berau Coal has been developed a learning platform, named SINTESIS+ and SID. The aims in development of those platforms are; (1) as a operational and HSE-themed learning platform, (2) toincrease capacity and to build HSE and operational competencies, (3) to increase operational control for competencies related to entry permit, work permit, license, and specialization, and (4) to intervene employees’ behaviour to build safety culture. Features and contents that has been embedded in SINTESIS+ are online learning with multimedia materials, online testing with real time result, webinar, incident and mining operational news, repositories for employees’ portfolio, event and training registration, integrated with SID to recordemployees’ historical competency-related data, and sustainable process to increase HSE awareness. Since its launching, SINTESIS+ has been accessed by 7867 employees, tested for 1024 exams, conducted webinar that participated by 330 employees, and run more effective and efficient processes. Impacts from integration process with SID are the increase of compliance level for competencies to 98% and the increase of process control efficiency. With those increments, beside the employees’ compency and HSE awareness is increased, hoped to lower incident rate. In the future, to improve access to the platform, Berau Coal is willing to develop mobile apps forSINTESIS+.